Dimensions of Communication Breakdown in Digitally Mediated Relationships - Grigoryan, Mariam; Tóth, Bálint (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore the underlying dimensions, triggers, and relational consequences of communication breakdown in digitally mediated romantic relationships. Methods and Materials: The study employed a qualitative, descriptive–interpretive design based on semi-structured interviews with 25 participants (aged 22–43) residing in Hungary, who were currently or recently engaged in digitally mediated romantic relationships. Participants were selected through purposive sampling to ensure diversity in relationship status and digital communication usage. Data were collected through in-depth, open-ended interviews focusing on experiences of misunderstanding, conflict, and emotional distance in digital interactions. The interviews continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed thematically using NVivo 14 software. Through an inductive coding process, emerging patterns were categorized into main themes and subthemes reflecting the nature and mechanisms of communication breakdown. Findings: The thematic analysis yielded four core dimensions of communication breakdown: (1) message ambiguity and misinterpretation, characterized by unclear tone, emotional detachment, and misread digital cues; (2) conflict escalation and digital triggers, including public exposure, reactive messaging, and asynchronous argument cycles; (3) emotional disconnection and relationship drift, reflected in reduced intimacy, digital fatigue, and avoidance behaviors; and (4) technological mediation barriers, involving platform fragmentation, algorithmic interference, and privacy-related constraints. The results indicated that digital communication both enables and destabilizes intimacy by amplifying emotional uncertainty and reducing contextual understanding. Conclusion: Findings highlight the paradoxical role of technology as both a facilitator and disruptor of intimacy in modern relationships. Effective digital communication requires emotional regulation, boundary awareness, and mindful technology use. Addressing the psychological and technical dimensions of digital interaction can enhance relational stability and prevent emotional estrangement among partners.